Cytomorphological Study of Thyroid Nodule and Categorization According to The Bethesda System and Its Histopathological Correlation - Rupareliya, Nikita; Patel, Prashant R; Bhagat, Vasudha M; Neb, Vimpy (Annals of Pathology and Laboratory Medicine, 2020)
Background: Among an endocrine disorder, thyroid disorders are most commonly encountered disorder in routine clinical practice. Clinically it is quite difficult to evaluate thyroid lesion and reach clinical diagnosis. FNAC (Fine needle aspiration cytology) of thyroid is commonly performed and most effective tool for diagnosis and management of patient with thyroid nodule. Present study was conducted in department of pathology, government medical college, Surat. Our main aims and objectives are to report thyroid cytology smears by TBSRTC in to various diagnostic categories and to correlate these with histopathological findings. Material and method: In the present study FNAC was performed on total 250 cases that were presented with thyroid swelling. These cases categorized according to TBSRTC and cytological diagnosis was correlated histopathologically in total 21 cases. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated. Results: FNAC was carried out in 250 cases, diagnostic categories includes 5.20% non-diagnostic, 87.60% benign, 2.80% Atypia of Undetermined Significance or Follicular Lesion of Undetermined Significance, 2.40% follicular neoplasm or suspicious for follicular neoplasm, 1.60% suspicious for malignancy and 0.40% malignant lesions. Subsequent histopathological correlation was possible in 21 cases. In present study accuracy, sensitivity, specificity, positive predictive value and negative predictive value of FNAC in diagnosis of thyroid were 95%, 85.71%, 100%, 100% and 92.85% respectively. Conclusion: Standardized categorical Bethesda systems for reporting thyroid FNAC can make results easier to understand and interpret for clinicians and give clear indications for therapeutic action.